Prognostic value of CHADS2 and CHA2DS2-VASc scores for post-discharge outcomes in patients with acute coronary syndrome undergoing percutaneous coronary intervention. Issue 30 (24th July 2020) - Ma, Xiaoteng; Shao, Qiaoyu; Dong, Lisha; Cheng, Yujing; Lv, Sai; Shen, Hua; Liang, Jing; Wang, Zhijian; Zhou, Yujie
Abstract : Abstract: The CHADS2 and CHA2 DS2 -VASc scores were initially developed to assess the risk of stroke or systemic embolism in patients with atrial fibrillation (AF). Recently, these two scoring systems have been demonstrated to predict long- and short-term cardiovascular (CV) outcomes in many patient cohorts. However, to the best of our knowledge, their prognostic value has not been fully elucidated in patients with acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI). This study aimed to investigate the association of CHADS2 and CHA2 DS2 -VASc scores with CV outcomes in such patients. We included a total of 915 ACS patients undergoing PCI in this study. CHADS2 and CHA2 DS2 -VASc scores were calculated from data collected before discharge. The primary endpoint was defined as a composite of major adverse CV events (MACE) including overall death, nonfatal stroke, nonfatal myocardial infarction (MI) and unplanned repeat revascularization. We assessed MACE's relationship to CHADS2 and CHA2 DS2 -VASc scores using Cox proportional-hazard regression analyses. Mean follow-up duration was 918 days. MACE occurred in 167 (18.3%) patients. A higher CHADS2 score was associated with reduced event-free survival (EFS) from MACE (logrank test, P  = .007) with differences potentiated if stratified by CHA2 DS2 -VASc score (logrank test, P  < .001). Univariate analysis showed that both CHADS2 and CHA2 DS2 -VASc scores were good predictors of MACE. In the multivariate Cox proportional-hazard regression analysis, CHA2 DS2 -VASc score (hazard ratio [HR], 1.15; 95% confidence interval [CI] 1.04–1.27; P  = .007) remained a useful predictor of MACE; however, CHADS2 score was no longer associated with increased risk of MACE. C-statistics for CHA2 DS2 -VASc score, GRACE (Global Registry of Acute Coronary Events) hospital discharge risk score (GRACE Score) and SYNTAX (Synergy between PCI with TAXUS and Cardiac Surgery) Score II (SS II) in predicting MACE were 0.614, 0.598, and 0.609, respectively. CHA2 DS2 -VASc score was an independent and significant predictor of MACE in ACS patients undergoing PCI, and its discriminatory performance was not inferior to those of GRACE Score and SS II.